Building Entrepreneurial Character and Marketing Talents In Primary School Students Through the Market Day Program - Maharani, Andi Nur Dean; Sutomo, Maskuri; Parani, Syamsul Bahri Dg.; Farid (Journal of Humanities, Community Service, and Empowerment, 2024)
The aim of this research is to determine the benefits of character building and developing the entrepreneurial spirit of students at SD Inpres 3 Ulatan in the Market Day program. The Market Day program is an entrepreneurship program to develop students' character. Within the scope of education, students must always be directed to change themselves through a creative and innovative spirit through quality superior programs. In elementary schools, this concept is important in suppressing the flow of entrepreneurship and creating superior competitive people. The research method used is a descriptive qualitative method. Data collection was carried out using primary data collection techniques; namely, the researcher directly took data from the field relating to implementation problems by directly reviewing the planning and implementation activities of market day at school, conducting interviews with school principals, teachers, parents, and students, as well as taking documentation in the form of supporting photos during Market Day activities. The informants in this research were students who were involved as buyers, teachers, parents, students, and school principals. The research results show that the implementation of Market Day is one of the programs implemented at SD Inpres 3 Ulatan, Parigi Moutong district to develop students' entrepreneurial spirit and mentality. In addition, teachers use contextual activities to improve students' skills.